2014
DOI: 10.1007/s11262-014-1122-4
|View full text |Cite
|
Sign up to set email alerts
|

Complete genomic characterization of a porcine reproductive and respiratory syndrome virus isolate in Xinjiang province of China

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is a swine disease of major economic importance that causes reproductive and respiratory problems in pigs. In the present study, one strain of porcine reproductive and respiratory syndrome virus (PRRSV) was isolated in Xinjiang province, Northwest China, designated XJu-1. The full-length genome of XJu-1 was found to be 14,987 nucleotides in length, including the poly(A) tail. Comparative analysis with the genomic sequences of type 2 isolates revealed that XJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Notably, our isolates have same additional 120 amino acid deletion at positions 628 to 747 of nsp2 . BLAST and phylogenetic analyses showed that at least 11 highly homologous viruses with the new genetic feature have been isolated in different regions of China from 2012 to 2017 [38,39,40]. These variants form a new branch within the HP-PRRSV subtype, suggesting that a new group of HP-PRRSV variants is circulating in Chinese swine herds for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our isolates have same additional 120 amino acid deletion at positions 628 to 747 of nsp2 . BLAST and phylogenetic analyses showed that at least 11 highly homologous viruses with the new genetic feature have been isolated in different regions of China from 2012 to 2017 [38,39,40]. These variants form a new branch within the HP-PRRSV subtype, suggesting that a new group of HP-PRRSV variants is circulating in Chinese swine herds for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…Table shows that variation in the region of Nsp2 that is nonessential for virus replication is the main factor contributing to genetic diversity of the PRRSV genome. Moreover, BLAST analysis showed that there were similar strains isolated in Xinjiang and Guangdong Province, but the pathogenicity of the isolated strains is not known (Xia et al., ; Yu et al., ).…”
Section: Discussionmentioning
confidence: 99%